De Architectura (1599) van Charles De Beste. Het vitruvianisme in de Nederlanden in de zestiende eeuw (Bulletin KNOB, 1995)
An unknown manuscript in the Koninklijke Bibliotheek (Royal Library) of Brussels (ms. II 7617) by the Bruges mason/bricklayer Charles De Beste: Architectura. Dat is Constelicke Bouwijnghen huijt die Antijcken Ende Modernen of 1599 forms a significant addition to our knowledge of Vitruvianism and Dutch theory of architecture in the sixteenth century.The work is not a translation of De Architectura Libri Decem, but on the basis of sixteenth-century commentaries on Vitruvius and followers it deals with a diversity of subjects from classical and contemporary architecture. Occasionally the texts are supplemented with De Beste's own, sometimes critical, observations and references to the situation in the Netherlands in general and in Bruges in particular.De Beste's treatise on architecture consists of eight books, devoted to arithmetics, geometry, astronomical instruments, sundials, architecture, perspective, fortress-building and artillery, respectively. At times the contents and illustrations of De Beste's treatise, dedicated to interested devotees of architecture, are quite close to contemporary northern building practice, whereas in other cases they are relatively theoretical in character and based on outdated examples.The variety in contents of the themes and the size of the manuscript, comprising a total of 578 folios, are a clear indication that the usual interpretations of the reception of Vitruvius and his commentators in Dutch sixteenth-century theory of architecture are no longer tenable. In these interpretations, mainly based on the printed documents of Coecke van Aelst and Vredeman de Vries, Dutch translations and commentaries are one-sidedly explained as practical examples for craftsmen for the application of colonnades and ornaments.Although Pieter Coecke van Aelst and Hans Vredeman de Vries dedicated their well-known treatises on architecture to craftsmen, these works - as the author puts it - were first and foremost meant for the group of art-loving enthusiasts and commissioners to whom De Beste had turned. Moreover, traces of other architectonic subjects dealt with by Vitruvius and followers, covering more than just colonnades, are to be recognized in the treatises on architecture of Pieter Coecke van Aelst and Vredeman de Vries. Consequently, the conclusion is that the manuscript of De Beste does not imply a break with the tradition of the ‘book on columns’, but is the continuation of a wider Vitruvian tradition in the Netherlands of the sixteenth century, which the selective works in print are also part of. Finally, a hypothesis follows on the question what objective Coecke van Aelst, Vredeman de Vries and Charles de Beste had in mind when compiling their various treatises on architecture.An article on De Beste's comments on a few buildings in Bruges and on his instructions for the iconography of tombs was published in Handelingen van het Genootschap voor Geschiedenis jaargang 131 (1994): 'De Architectura (1599) van Charles De Beste (1599). Een onbekend architectuurtraktaat van een Brugse bouwmeester' (The Architectura (1599) of Charles De Beste (1599). An unknown treatise on architecture by a Bruges mason/ bricklayer) by C. van den Heuvel.